The Relationship between Serum Uric Acid Levels and Early Mortality in Chronic Obstructive Pulmonary Disease Cases during Exacerbation - Yüceer, Omer; Büyükbayram, Gökhan; Oymak, Fatma Sema (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Aim: In this study, it was aimed to compare the levels of serum uric acid and uric acid/creatinine ratios in patients with COPD during an attack or in stable COPD, and to show whether serum uric acid and uric acid/creatinine ratios are associated with early mortality in COPD patients during an acute attack.Materials and Methods: In this study, COPD acute attack (n=125) and stable COPD (n=30) patients were evaluated. The data of these patients were obtained from patient files and computer records. COPD diagnosis and severity assessment were made according to the GOLD 2006 guideline. Participants' age, gender, body mass index, pulmonary function test, arterial blood gas, uric acid, creatinine values ​​and comorbidity information were recorded in the previously prepared Case Data Form.Results: It was determined that the uric acid (p˂0.001) and uric acid/creatinine (p˂0.001) levels of the patients in the acute attack group were significantly higher than the levels of the patients in the stable group. The attack group was divided into two subgroups according to certain cut-off points for uric acid (˃6 mg/dl for women and ˃7 mg/dl for men) and uric acid/creatinine ratio (median value 7.10). According to this categorization, it was determined that there was no statistically significant relationship between uric acid level (odds ratio 2.985 [95% confidence interval 0.618-14,151]) and early mortality risk.Conclusion: The results of this study showed that the uric acid and uric acid/creatinine levels in the attack group were higher than the levels in the stable group, but these parameters were not associated with early mortality.